Evaluasi Kebijakan Dana Desa untuk Penanggulangan Kemiskinan dan Peningkatan Infrastruktur Pelayanan Dasar Air Minum serta Sanitasi Kabupaten/Kota di Indonesia - Muhamad Chehafudin; Samodra Wibawa; Soesilo Wibowo (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2022)
This study aims to analyze the effect of the Village Fund on poverty alleviation and improvement of basic infrastructure services for drinking water and sanitation in districts and cities in Indonesia. The need for evaluation of the Village Fund policy is a consequence of the implementation of fiscal decentralization to villages based on Law no. 6/2014. This policy has implications for an increase in transfer funds to villages of more than IDR 329 trillion cumulatively. Theoretically, fiscal decentralization to villages should improve public services and accelerate poverty reduction through local preferences matching and more efficient allocations. This research was a quantitative study using path analysis to test the hypotheses. Data were obtained from BPS and the Ministry of Finance for all districts/cities receiving Village Fund. The results show that The Village Fund had a significant effect on poverty reduc-tion nationally, although its contribution was very small, and the effect was not significant in districts/cities with low fiscal capacity. The Village Funds had an effect on increasing drinking water but not significant, on the other hand, it had a significant effect on districts/cities with medium or low fiscal capacity with low poverty rate. The Village Fund had an effect on improving sanitation but it was not significant nationally or in all districts/cities. The Village Fund for drinking water had no significant effect on poverty reduction nationally and for all districts/cities. The Village Fund for sanitation had no effect on poverty reduction nationally or in all districts/cities but it had an effect on districts/cities with low fiscal capacity and poverty rate even though it was not significant. The implementation of the Village Fund policy needs to consider the fiscal capacity and diversity of regional characteristics in order to make the effectiveness of the Village Fund more optimal.